A Histopathological Study of Skin Lesions in Individuals with Oculocutaneous Albinism in Togo in 2019 - Bayaki Saka; Julienne Noude Teclessou; Sefako Abla Akakpo; Piham Gnossike; Kwamé Doh; Saliou Adam; Abas Mouhari-Toure; Garba Mahamadou; Panawé Kassang; Yvette Elegbede Moise; Tchin Darre; Koussake Kombate; et al. (Journal of Skin Cancer)
Objective. The aim of this study was to study the histopathological patterns of skin lesions in persons with albinism (PWA) in Togo in 2019. Method. During two mobile skin care clinics in 2019, biopsies/excisional biopsies were performed in PWA in case of clinical doubt or in front of lesions suspected to be cancerous for histological examination. Anatomopathological reports were thus analysed. Results. During the two mobile skin care clinics, 115 biopsies/excisional biopsies were carried out in 79 PWA, with a mean age of 24 ± 16.1 years. Histological examination led to a diagnosis in 110 cases (95.6%) and was inconclusive in 5 cases (4 cases of uncertain histological diagnosis and one case of nonspecific histological lesions). Fourteen different histological diagnoses were made, with a frequency ranging from 0.9% (one case) to 26.9% (31 cases). The four most frequent diagnoses in descending order were basal cell carcinomas (BCCs) (31 cases; 26.9%), invasive squamous cell carcinomas (SCCs) or Bowen’s disease (23 cases; 20%), keratosis (20 cases; 17.3%), and cysts (seven cases; 6.1%). The 54 skin carcinomas were diagnosed in 33 (41.8%) of the 79 patients who underwent skin biopsies/excisional biopsies. The BCC/SCC ratio was 1.3. No cases of cutaneous melanoma had been diagnosed. Conclusion. Skin cancers represent the main histological diagnosis in PWA (46.9%) in Togo in 2019. The pattern of cutaneous malignancies in PWA shows the same trend as that seen in Caucasians with a predominance of basal cell carcinomas.